2008
DOI: 10.1080/01140671.2008.9651468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pistil receptivity, pollen mixtures, and pollen application distances on fruit set of pistachios (Pistacia vera)

Abstract: This study was carried out at the pistachio (Pistacia vera) orchards of Ceylanpınar State Farm, Turkey. The cultivar 'Siirt' and Male 13 were used in the experiments. The aim of the study was to investigate the effect of pistil receptivity, pollen mixtures, and pollen application distances on fruit set using artificial pollination in pistachios. To determine the receptivity of female flowers, anthesis was accepted as day 0, and then one application was carried out on 0, 2, and 4 days after anthesis; and repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The amount of viable pollen loaded on the stigma is the first step in pollination (Wilcock and Neiland, 2002). Acar and Eti (2008) reported 14 or 15 pollen grains per stigma is adequate for pollination in pistachio. On germination, the pollen tube grows the length of the style to the micropyle, the opening in the ovule's outer layer.…”
mentioning
confidence: 99%
“…The amount of viable pollen loaded on the stigma is the first step in pollination (Wilcock and Neiland, 2002). Acar and Eti (2008) reported 14 or 15 pollen grains per stigma is adequate for pollination in pistachio. On germination, the pollen tube grows the length of the style to the micropyle, the opening in the ovule's outer layer.…”
mentioning
confidence: 99%
“…However, several pollination experiments have found a reduction in reproductive success and several mechanisms have been proposed to explain that decrease (Young and Young 1992). For example, large pollen loads on flowers may have negative effects on pollen tube growth (Cruzan et al 1986;Acar and Eti 2008). Our second pollination experiment showed that this was not the cause of lower fruit set because fruits developing from hand-pollinated flowers had proportionally more grown pollen tubes than fruits from natural-pollinated flowers.…”
Section: Discussionmentioning
confidence: 80%
“…Successful pollination is depending on a range of factors during pollen application. The amount of manually applied pollen can affect the fruit set (Acar & Eti, 2008). The optimal pollen amount needed for fertilization can depend on environmental conditions (Peet & Bartholemew, 1996) and species (Acar & Eti, 2008;Janse & Verhaegh, 1993).…”
Section: Text A1: the Process Of Hand Pollinationmentioning
confidence: 99%
“…The amount of manually applied pollen can affect the fruit set (Acar & Eti, 2008). The optimal pollen amount needed for fertilization can depend on environmental conditions (Peet & Bartholemew, 1996) and species (Acar & Eti, 2008;Janse & Verhaegh, 1993). In natural pollination, pollen is applied gradually in contrast to hand pollination, where great pollen amounts are applied at once (Fazzino et al, 2011).…”
Section: Text A1: the Process Of Hand Pollinationmentioning
confidence: 99%
See 1 more Smart Citation